ABNORMAL VASCULAR BUNDLES regulates cell proliferation and procambium cell establishment during aerial organ development in rice - Ma, Ling; Sang, Xianchun; Zhang, Ting; Yu, Zhanyang; Li, Yunfeng; Zhao, Fangming; Wang, Zhongwei; Wang, Yantong; Yu, Peng; Wang, Nan; Zhang, Changwei; Ling, Yinghua; et al. (The New phytologist, 2017)
To understand the molecular mechanisms of rice aerial organ development, we identified a mutant gene that caused a significant decrease in the width of aerial organs, termed ABNORMAL VASCULAR BUNDLES (AVB). Histological analysis showed that the slender aerial organs were caused by cell number reduction. In avb, the number of vascular bundles in aerial organs was reduced, whereas the area of the vascular bundles was increased. Ploidy analysis and the in situ expression patterns of histone H4 confirmed that cell proliferation was impaired during lateral primordia development, whereas procambium cells showed a greater ability to undergo cell division in avb. RNA sequencing (RNA-seq) showed that the development process was affected in avb. Map-based cloning and genetic complementation demonstrated that AVB encodes a land plant conserved protein with unknown functions. Our research shows that AVB is involved in the maintenance of the normal cell division pattern in lateral primordia development and that the AVB gene is required for procambium establishment following auxin signaling.